DETERMINAN ANGKA PARTISIPASI MURNI: STUDI PADA PENDUDUK MISKIN TINGKAT PROVINSI DI INDONESIA - Hermawan, Wawan; Maipita, Indra; Wahyudi, Setyo Tri (Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
One of the success of education can be seen in the development of the Pure Participation Rate (APM). Positive economic growth and a reduction in poverty levels raise questions on what factors affect the APM at the elementary, junior high and high school levels for the poor in Indonesia. The panel data model for 29 provinces and the 2011-2015 timeframe forms the basis of research data. The estimation results of the model show the coefficient of income per capita is very elastic and affects the APM for each level of education in Indonesia. Government spending on education still has the effect of increasing the APM for primary school, junior and senior high school education but has an impact that actually reduces the APM. Inequality increases the APM in Indonesia at the elementary and high school levels, whereas at the junior high level it actually lowers the APM. Finally, age at each level has an influence on middle and high school levels, but is different for elementary school levels. Keyword: Pure Participation Rate, Per capita income, government expenditure and Equality